2016
DOI: 10.1007/s00402-016-2583-9
|View full text |Cite
|
Sign up to set email alerts
|

Cementless metaphyseal sleeves without stem in revision total knee arthroplasty

Abstract: We found that the prostheses were overall well fixed and patients' AKSS increased significantly. Many patients had pain conditions, both comorbid pain and pain that might be alignment-related, and adding a stem thus seems to be a good idea in terms of alignment. Level of evidence Level IV, case series without control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 18 publications
1
37
0
1
Order By: Relevance
“…Fourth, the overall alignment of the tibial construct remained constant throughout the study. Gottsche et al reported a wide variation in the tibio‐femoral angle of the patients investigated and patients with increase valgus reported worse patients reported outcomes. They speculated that this wide variation could be related to the fact that the sleeves were used to conduct the tibial cuts instead of using the manufacturers allocated cutting guides.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourth, the overall alignment of the tibial construct remained constant throughout the study. Gottsche et al reported a wide variation in the tibio‐femoral angle of the patients investigated and patients with increase valgus reported worse patients reported outcomes. They speculated that this wide variation could be related to the fact that the sleeves were used to conduct the tibial cuts instead of using the manufacturers allocated cutting guides.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported on the use of metaphyseal fixation with sleeves only to augment rTKR reconstruction of AORI type 2 and 3 bone defects . Although considered promising, the results are difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osseous defects of cases coming to rTKR are commonly categorized in accordance with the Anderson Orthopaedic Research Institute (AORI) Classification . AORI IIB defects, which consist of cancellous and cortical metaphyseal bone loss in both tibial/femoral condyles, are most common and are encountered in up to 42% of rTKR's …”
mentioning
confidence: 99%